Aristolochia mishuyacensis (Aristolochiaceae), a new record for Ecuador, with taxonomic notes. Issue 1 (30th November 2018) - Pérez, Álvaro J.; González, Favio; Cevallos, Daniela; Zapata, Nicolás; Santillán, Washington; Whitehurst, Lauren; Worthy, Samantha J.; Romoleroux, Katya; Burgess, Kevin
ABSTRACT: Aristolochia mishuyacensis is recorded for the first time in the Ecuadorian Amazon. Two specimens were collected in two banks of black water tributaries of the Yasuní river, Yasuní National Park. This species is currently distributed in Bolivia, Brazil, Colombia, Ecuador, and Peru, below 200 m. An updated description and images of the species are provided, and its relationships with other species are discussed.